This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rewrite the equation as: t 4 + 4 t 3 + t 2 + 2 t + 2 5 = a 2
Let f ( t ) = t 4 + 4 t 3 + t 2 + 2 t + 2 5 : our goal consists in finding t for which f ( t ) is a square. We can write:
{ f ( t ) > ( t 2 + 2 t − 3 ) 2 f ( t ) < ( t 2 + 2 t + 1 ) 2 t = − 2 ( 1 ) t = − 2 , − 1 , 0 , 1 , 2 ( 2 ) → ( t 2 + 2 t − 3 ) 2 < f ( t ) < ( t 2 + 2 t + 1 ) 2 t = − 2 , − 1 , 0 , 1 , 2
The value for which t does not satisfy the inequality can be find solving each inequality. For instance the ( 2 ) : t 4 + 4 t 3 + t 2 + 2 t + 2 5 > ( t 2 + 2 t + 1 ) 2 → 5 t 2 + 2 t − 2 4 > 0 → t < − 5 1 2 ∨ t > 2 implying that t = − 2 , − 1 , 0 , 1 , 2 . From the inequality ( t 2 + 2 t − 3 ) 2 < f ( t ) < ( t 2 + 2 t + 1 ) 2 we know that for almost all values of t , f ( t ) is a number between two square which differ from 4. Since f ( t ) must be a square, we have only 3 possibilities:
f ( t ) = ( t 2 + 2 t − 2 ) 2 that has solutions t = − 3 ∨ t = − 7
f ( t ) = ( t 2 + 2 t − 1 ) 2 that has no solutions in Z
f ( t ) = ( t 2 + 2 t ) 2 that has no solutions in Z
Finally, we have to check by hand the cases t = − 2 , − 1 , 0 , 1 , 2 .
The solutions are ( a , t ) = ( ± 1 , − 3 9 ) , ( ± 3 , − 2 ) , ( ± 5 , 0 ) , ( ± 9 , 2 ) , ( ± 3 3 , − 7 ) , so the answer is 1 0